Comparative study of pap smear and microbiological pattern in bacterial vaginosis - J., Girishma; M., Rupakala B.; Chavan, Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Bacterial vaginosis is the most common cause of vaginal discharge among women in reproductive age group. It is characterized by an increased vaginal pH and loss of normal lactobacilli and overgrowth of anaerobes like Gardnerella vaginalis and other gram-negative rods. Purpose of this study is to compare the characteristics of pap smear and microbiological pattern in patients with abnormal vaginal discharge. Methods: The study was conducted in the Department of Gynecology and Obstetrics of Rajarajeswari Medical College and Hospital (RRMCH) Bangalore, India. All patients with vaginal discharge were included in the study. Vaginal discharge samples were sent to gram staining, culture and pap smear examination. Results: Of the 52 patients, 18 patients (34.6%) showed positive for bacterial vaginosis according to Nugent’s score. Of the 18 patients with positive Gram stains, 8 of them were positive for bacterial vaginosis according to pap’s smear (44%) and 10 had negative pap smears. In our study, of the 18 patients with positive Gram stains, 14 (77%) of them were positive for bacterial vaginosis according to culture. Conclusions: In the present study we found out that correlation of gram stain and pap smear was 44% whereas correlation of gram stain and culture was 77%. Hence, we conclude that gram stain and culture are preferred for the diagnosis of bacterial vaginosis rather than the pap smear evaluation.